Re-emergence of Monkeypox in Nigeria: a cause for concern and public enlightenment (2018)
Monkey pox infection is a zoonotic infection transmitted by direct or indirect contact with blood, body fluids and lesions of an infected animal. Human to human spread of Monkey pox has been described and infection is usually self-limiting, with an incubation period of 6-16 days. In Nigeria, the last case of monkey pox infection was recorded over 46 years ago. The recent emergence in Nigeria occurred in the year 2017 and was reported to have spread to 24 states with 228 suspected individuals affected. Laboratory diagnosis, as well as management and prevention of monkey pox infection in Nigeria, remain challenging as Nigeria is a resource-poor country with limited infrastructure, technical skill and training which is required in making a diagnosis. The ability of the monkey pox virus to evolve, its potential bioterrorism potential, as well as its recent emergence in Nigeria further justifies the need for improving the understanding of the presentation and prevention of monkey pox infection.